Proteomic profiling of the brain of mice with experimental cerebral malaria - Moussa, E; Huang, H; Ahras, M; Lall, A; Thezenas, M; Fischer, R; Kessler, B; Pain, A; Billker, O; Casals-Pascual, C (Elsevier, 2017)
Cerebral malaria (CM) is a severe neurological complication of malaria infection in both adults and children. In pursuit of effective treatment of CM, clinical studies, postmortem analysis and animal models have been employed to understand the pathology and identify effective interventions. In this study, a shotgun proteomics analysis was conducted to profile the proteomic signature of the brain tissue of mice with experimental cerebral malaria (ECM) in order to further understand the underlying pathology. To identify CM-associated response, proteomic signatures of the brains of C57/Bl6N mice infected with P. berghei ANKA that developed neurological syndrome were compared to those of mice infected with P. berghei NK65 that developed equally high parasite burdens without neurological signs, and to those of non-infected mice. The results show that the CM-associated response in mice that developed neurological signs comprise mainly acute-phase reaction and coagulation cascade activation, and indicate the leakage of plasma proteins into the brain parenchyma.Cerebral malaria (CM) remains a major cause of death in children. The majority of these deaths occur in sub-Saharan Africa. Even with adequate access to treatment, mortality remains high and neurological sequelae can be found in up to 20% of survivors. No adjuvant treatment to date has been shown to reduce mortality and the pathophysiology of CM is largely unknown. Experimental cerebral malaria (ECM) is a well-established model that may contribute to identify and test druggable targets. In this study we have identified the disruption of the blood-brain barrier following inflammatory and vascular injury as a mechanism of disease. In this study we report a number of proteins that could be validated as potential biomarkers of ECM. Further studies, will be required to validate the clinical relevance of these biomarkers in human CM.